Diacetyl-induced bronchiolitis obliterans involves ubiquitin C upregulation and fibrosis-related gene activation in rats - Wang, Hailian; Jiang, Wen; Xiao, Junchao; Geng, Yan; Ye, Qing; Ge, Wei (Frontiers in Pharmacology, 2025)
IntroductionBronchiolitis obliterans (BO) is an irreversible, chronic obstructive pulmonary disease with inflammation and fibrosis causing bronchiolar narrowing. Inhaling diacetyl (DA) can result in BO in humans.MethodsWe aimed to investigate the relationship between fibrosis-related gene expression and ubiquitin C (UbC) regulation in a rat model of BO following a single DA instillation, by examining lung histopathology, UbC protein levels, and transcriptomic changes.ResultsAfter DA exposure, rat bronchioles exhibited marked inflammation, increased collagen deposition, airway fibrosis, and obstruction. These changes were confirmed by histology and semi-quantitative image analysis. UbC protein levels were significantly elevated in a time-dependent manner. RNA sequencing revealed significant alterations in gene expression and enrichment of multiple molecular functions and biological processes in BO rats compared with controls, including pathways related to fibrosis formation and ubiquitin dysregulation. Quantitative PCR (qPCR) validation further confirmed the transcriptomic results, showing significant upregulation of Ube2t and Fap and downregulation of Cyp1a1, consistent with enhanced ubiquitin activity, fibroblast activation, and impaired oxidative stress regulation.DiscussionThese findings indicate that DA instillation induces early BO-like changes, disrupts ubiquitin regulation, and increases UbC expression, potentially through oxidative stress–related mechanisms. A better understanding of ubiquitin regulation (particularly UbC) may provide novel molecular targets for therapeutic intervention in BO.